Edukasi Mahasiswa Tentang Pengaruh Bias Availability, Framing, Anchoring, Blind Spot, dan Fear Of Missing Out (FOMO) Terhadap Impulsive Buying Pada Jenis Pembayaran Paylater - Sabrina Fitria Rahmadani; Ariqinanty, Nadila Zahra; Inan Safanah Astin; Ardhiani Fadhila; Sri Mulyantini, (Journal Of Human And Education (JAHE), 2024)
This educational program socialization activity aims to increase knowledge and understanding related to financial behavioral biases. The financial behavioral bias material provided and taught is availability bias, framing bias, anchoring bias, blind spot bias, and FOMO. In addition, the influence of the five biases on impulsive buying behavior on the paylater system. The object of this research is UPNVJ 2024 Merdeka Student Exchange (PMM) students. The method of providing material is done through coordination with students, the implementation of educational programs containing pre-test quizzes, delivery of material from powerpoint, discussion sessions, post-test quizzes and evaluation of feedback through google form. The results of this socialization activity show that PMM students are enthusiastic in discussing the material that has been presented, an increase in quiz results from the pre-test and post-test, each of which amounts to 12 questions of around 19% from the pre-test results of 51% and post-test 70% from 100%. This shows an increase in understanding related to financial behavior biases. Based on feedback, positive results were obtained from the participants' PMM students related to the material education provided and the overall activities and suggestions given, participants expecting that this socialization program activity can be continued better.